The Nova Scotia Experiment in Labour Management Relations - Brookbank, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1965)
The following study constitutes a breakthrough in the field of behaviour sciences applied to labour-management relations. This paper is a description and an interpretation of the organizational pattern and the type of behaviour dynamics which emerged in the course of the experiment under the guidance of the Institute of Public Affairs at Dalhousie University.